The Future of Law Professors and Comparative Law - Pardolesi, Roberto (2014)
In this paper, the authors analyze the positions on the objectives of Comparative Law as an autonomous discipline, as well as the intersection between law and economics and its implications for future studies of law. this is studied in relation not only to what is Law, but with what it should be. ending the authors propose a new perspective for comparatists lawyers, seeking to revitalize legal research.